Gallblader ultrasound study in pregnant women - Palacios, Miguel (2015)
OBJECTIVE: To determine the value of gallbladder ultrasound study in the pregnant woman. DESIGN: Prospective longitudinal study. MATERIAL AND METHODS: The gallbladder was studied in 120 pregnant woman with ultrasound 3,5Mhz convex transductor. RESULTS: Gallbladder pathology was detected in 20 patients (16,6%), gallstones in l6 patients (13,33%), gallbladder sludge in 3 patients (2,5%) and polyposis in one patient (0,83%). No statistical difference was found between women in their first or subsequent pregnancies, P>O,5. CONCLUSIONS: The high proportion of gallbladder pathology, mainly lithiasis, justifies routine ultrasound gallbladder exploration in all pregnant women.